Delivery in a woman with ileostomy after total coloproctectomy (clinical case) - P.A. Kuznetsov; A.S. Olenev; A.V. Tyagunova; L.S. Dzhokhadze; L.V. Kornev (РМЖ. Мать и дитя, 2019)
P.A. Kuznetsov1–3, A.S. Olenev2, A.V. Tyagunova1, L.S. Dzhohadze1,3, L.V. Kornev2 1 Pirogov Russian National Research Medical University, Moscow, Russian Federation 2 City Hospital 24, Moscow, Russian Federation 3 Research Institute of Public Health and Medical Management, Moscow, Russian Federation There are no regulating guidelines on the management of pregnancy and childbirth in patients with ileostomy because these clinical scenarios are rare. These patients have no decline in fertility. However, pregnancy is associated with stoma problems. Delivery method choice remains a concern. There are several potential complications of vaginal delivery, i. e., ruptures of pelvic scar tissues behind posterior vaginal wall and stoma leakage under dramatic fluctuations of intra-abdominal pressure. The paper describes successful pregnancy in a woman with total coloproctectomy and ileostomy for sigmoid cancer resulted from ulcerative colitis and provides a basis for optimal delivery method. Keywords: stoma, coloproctectomy, ulcerative colitis, sigmoid adenocarcinoma, delivery. For citation: Kuznetsov P.A., Olenev A.S., Tyagunova A.V. et al. Delivery in a woman with ileostomy after total coloproctectomy (clinical case). Russian Journal of Woman and Child Health. 2019;2(3):262–264.